Experience of nature and times of silence as a resource to cope with the COVID-19 pandemic and their effects on psychological wellbeing—Findings from a continuous cross-sectional survey in Germany - Büssing, Arndt; Recchia, Daniela Rodrigues; Baumann, Klaus (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic with its lockdowns affected social relations and mental health conditions of people worldwide. We aimed to analyze the relevance of nature and times of silence as resources to cope with the pandemic. Of interest were how experiences of nature and times of silence are related to the perception of wondering awe and gratitude and psychological wellbeing and how these have changed during the different phases of the pandemic. Finally, we asked whether Nature/Silence would mediate the link between Awe/Gratitude and wellbeing. Methods A cross-sectional survey with standardized questionnaires (i.e., PCQ, GrAw-7, BMLSS-10, WHO-5) enrolling participants during the different phases of the COVID-19 pandemic was conducted. The total sample of 5,155 participants from Germany consisted of 65% women and 34% men, with a mean age of 45.0 ± 14.0 years. Results Directly after the first lockdown, Nature/Silence and Awe/Gratitude scores were high and decreased along with wellbeing with the onset of the second lockdown in winter 2020, while perceived burden constantly increased. Nature/Silence was rated lowest by people with reduced wellbeing (eta2 = 0.058) and feeling lonely or socially isolated (eta2 = 0.042). Predictor analyses revealed that wellbeing as a dependent variable was predicted best by corona-related perception of burden, Awe/Gratitude, reflection of life, and Nature/Silence and further by perceived changes in terms of relationships and spirituality (R2 = 0.55). In mediation analyses, Awe/Gratitude proved to be a significant predictor for Nature/Silence (β = 0.55, p< 0.0001) and wellbeing (β = 0.05, p < 0.0001). The mediation analysis explained 37% of the variability in the data. The direct influence of Awe/Gratitude on wellbeing was estimated as β = 0.09 (p < 0.0001), and the mediation effect of Nature/Silence on the link between Awe/Gratitude and wellbeing was significant, too (β = 0.03, p < 0.0001), explaining 25% of the total effect. Conclusion Nature/Silence and Awe/Gratitude were used as relevant resources during the pandemic, although they cannot fully buffer the negative effects of the social restrictions that resulted in decreases in wellbeing and increases in perceived burden. Perception of nature as a sensitizer of positive experiences particularly during difficult phases of life could be trained to stabilize wellbeing and thus to contribute to public health.